Detecting Land use/cover dynamics and land suitability mapping for Irbid governorate using an integrated approach - Mohammad, Alsharifa Hind; Odeh, Taleb; Halalsheh, Maha; Shatanawi, Khaldoun (Journal of Environmental Engineering and Landscape Management, 2021)
This research proposes to design an approach recognizing land use/cover change for Irbid governorate from 1985 to 2015 in 10 years period bases, with an agriculture suitability map using remote sensing and GIS. In this paper, ENVI6 was used to analyse Landsat images, which helps to understand the land uses’ classes. LULC Changes results showed an increase in urban land, from 2% in 1985 reached to 11% in 2015; soil and agricultural classes had declined, in 1985 they were 74% of the total area, and reduced to 67% in 2015. Irbid Governorate’s change detection results revealed that the decline of agriculture and rock land areas is due to the accelerated expansion of urbanization, which negatively affects agricultural lands. Modelling the area showed high suitability for agricultural activities, which should be considered for the upcoming plans.